Technology-facilitated domestic abuse in the UK: the experiences of victim-survivors and their interactions with services - Brookfield, Kathryn Amy (2025)
This thesis examines women’s experiences of technology-facilitated domestic abuse (TFDA) in the UK, a complex form of abuse at the intersection of historic manifestations of domestic abuse and modern-day digital society. This research draws on three data sets: a survey with 141 women with lived experience of TFDA, in-depth interviews with six women with lived experience of TFDA, and interviews with 16 professionals working in the domestic abuse sector. Participants hail from all four countries across the UK, making this one of the most comprehensive UK-based studies of TFDA to date. As well as documenting the types of TFDA women are experiencing during and post their relationship, this thesis also considers how TFDA shapes and disrupts women’s ability to interact with support services. Being under digital surveillance from an intimate partner limits, or sometimes prevents, women from accessing life-saving support, and consideration must be given to how services can continue to support women safely and effectively in the digital age. Once women are in touch with services, these services must also be equipped to support women in a way which accounts for the myriad dangers and harms caused by TFDA, especially during the delicate process of separation. This thesis concludes with practical recommendations for victim-survivors, the domestic abuse sector, other services (including the police and social services), the tech sector, and policy makers. It is hoped that the outputs from this research will be informative for those working in the tech sector, and with women impacted by TFDA, so that women can be supported more appropriately in the future.